Regimen durability in HIV-infected children and adolescents initiating first-line ART in a large public sector HIV cohort in South Africa - Bonawitz, Rachael (Trop Med Int Health, 2018)
INTRODUCTION: In April 2010 tenofovir and abacavir replaced stavudine in public-sector first-line antiretroviral therapy (ART) for children under 20 years old in South Africa. The association of both abacavir and tenofovir with fewer side-effects and toxicities compared to stavudine could translate to increased durability of tenofovir or abacavir-based regimens. We evaluated changes over time in regimen durability for pediatric patients 3 to 19 years of age at 8 public sector clinics in Johannesburg, South Africa. METHODS: Cohort analysis of treatment naïve, non-pregnant pediatric patients from 3 to 19 years old initiated on ART between April 2004-December 2013. First-line ART regimens before April 2010 consisted of stavudine or zidovudine with lamivudine and either efavirenz or nevirapine. Tenofovir and/or abacavir was substituted for stavudine after April 2010 in first-line ART. We evaluated the frequency and type of single-drug substitutions, treatment interruptions, and switches to second-line therapy. Fine and Gray competing risk regression models were used to evaluate the association of antiretroviral drug type with single-drug substitutions, treatment interruptions, and second-line switches in the first 24-months on treatment. RESULTS: 398 (15.3%) single-drug substitutions, 187 (7.2%) treatment interruptions and 86 (3.3%) switches to second-line therapy occurred among 2602 pediatric patients over 24-months on ART. Overall, the rate of single-drug substitutions started to increase in 2009, peaked in 2011 at 25%, then declined to 10% in 2013, well after the integration of tenofovir into pediatric regimens; no patients over the age of 3 were initiated on abacavir for first-line therapy. Competing risk regression models showed patients on zidovudine or stavudine had upwards of a 5-fold increase in single-drug substitution vs. patients initiated on tenofovir in the first 24-months on ART. Older adolescents also had a 2-3-fold increase in treatment interruptions and switches to second-line therapy compared to younger patients in the first 24-months on ART. CONCLUSIONS: The decline in single-drug substitutions is associated with introduction of tenofovir. Tenofovir use could improve regimen durability and treatment outcomes in resource-limited settings.